Biochar Adsorbents for Arsenic Removal from Water Environment: A Review - Srivastav, Arun Lal; Pham, Tien Duc; Izah, Sylvester Chibueze; Singh, Nirankar; Singh, Prabhat Kumar (Bulletin of environmental contamination and toxicology, 2022)
Arsenic intake can cause human health disorders to the lungs, urinary tract, kidney, liver, hyper-pigmentation, muscles, neurological and even cancer. Biochar is potent, economical and ecologically sound adsorbents for water purification. After surface modifications, adsorption capacity of biochar significantly increased due to high porosity and reactivity. Adsorption capacities of the biochar derived from the municipal solid waste and KOH mixed municipal solid waste were increased from 24.49 and 30.98 mg/g for arsenic adsorption. Complex formation, electrostatic behavior and ion exchange are important mechanisms for arsenic adsorption. Organic arsenic removal using biochar is a major challenge. Hence, more innovative research should be conducted to achieve one of the 17 sustainable development goals of the United Nations i.e. “ providing safe drinking water for all ”. This review is focused on the arsenic removal from water using pristine and modified biochar adsorbents. Recent advances in production methods of biochar adsorbents and mechanisms of arsenic removal from water are also illustrated.